ISLAM WASATHIYAH : RITUAL DAN MISTISISME JAWA TENGGER DALAM TRADISI PERKAWINAN - Fauziyah Putri (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2025)
Indonesian society is known for its cultural and religious diversity, with the majority of its population adhering to Islam. In the Tengger region of Java, there exists a unique blend of Islamic teachings and Hindu traditions, reflecting the application of the concept of Islam Wasathiyah (religious moderation). This study aims to analyze the rituals and mysticism in the Tengger Javanese marriage tradition, as well as the supporting and hindering factors in the implementation of Islam Wasathiyah in these practices. Despite the majority of the Tengger people being Hindu, the interaction between Islam and local culture has led to the phenomenon of interfaith marriages, which combine both traditional rituals and Islamic teachings. This research employs a post-positivist paradigm with a qualitative approach and a case study method conducted in the villages of Wonokerto and Ngadisari, Sukapura District, Probolinggo Regency. The findings of this study are expected to provide a deeper understanding of religious moderation in the context of local traditions and its impact on cultural diversity and interfaith harmony in Indonesia. Keyword : Islam Wasathiyah, Marriage Rituals, Tengger Java